The Joseph story between Egypt and Israel - Römer, Thomas, 1955-; Schmid, Konrad, 1965-; Bühler, Axel, 1992- (Archaeology and Bible ;, 2021)
"Within the context of the Torah, the Joseph story can be read as a transition that explains why Jacob and his family came to Egypt. However, if one looks at other texts of the Hebrew Bible, there is no mention of the Joseph story; instead, the arrival of the Israelites is said to be the result of the decision of a 'father' or of 'fathers' to go down do Egypt. Indeed, there are very few references to Joseph at all in the whole Hebrew Bible. Apparently, the Joseph story is not necessary for explaining why the Israelites found themselves in Egypt. The question therefore arises: Why was this story written, when, and for what audience? This volume offers an overview of the current discussion on the origins, composition, and historical contexts behind the Joseph narrative. There is a tendency to date the story (or its original version) to the Persian period, but this volume includes divergent voices about this issue. The volume also shows that scholarly discussion about the historical location of the Joseph story requires to bring together Egyptologists and biblical scholars."